The Impact of Using Gadgets and Social Media - Lale Sirin Rifdah Salsabila (Rifa'Institute, 2022)
Insomnia is part of the primary sleep disorder group, dyssomnia. Insomnia is the inability to meet the need for sleep both in quality and quantity due to difficulties in initiating and maintaining sleep. About 30% of adults suffer from insomnia, and 10% of adults suffer from severe insomnia. The purpose of this article is to determine the impact of gadget on the incidence of insomnia. The method used is systematic literature review. The result of this literature review is that the use of devices has an impact on the incidence of insomnia. The use of electronics deals with various aspects of sleep such as sleep quality, sleep duration, sleep mood and drowsiness during activities. This happens because of the habit of using electronic devices that shine brightly and highlight the eyes, this light can trigger or stimulate the brain to wake up and delay the desire to sleepInsomnia is part of the primary sleep disorder group, dyssomnia. Insomnia is the inability to meet the need for sleep both in quality and quantity due to difficulties in initiating and maintaining sleep. About 30% of adults suffer from insomnia, and 10% of adults suffer from severe insomnia. The purpose of this article is to determine the impact of gadget on the incidence of insomnia. The method used is systematic literature review. The result of this literature review is that the use of devices has an impact on the incidence of insomnia. The use of electronics deals with various aspects of sleep such as sleep quality, sleep duration, sleep mood and drowsiness during activities. This happens because of the habit of using electronic devices that shine brightly and highlight the eyes, this light can trigger or stimulate the brain to wake up and delay the desire to sleepInsomnia is part of the primary sleep disorder group, dyssomnia. Insomnia is the inability to meet the need for sleep both in quality and quantity due to difficulties in initiating and maintaining sleep. About 30% of adults suffer from insomnia, and 10% of adults suffer from severe insomnia. The purpose of this article is to determine the impact of gadget on the incidence of insomnia. The method used is systematic literature review. The result of this literature review is that the use of devices has an impact on the incidence of insomnia. The use of electronics deals with various aspects of sleep such as sleep quality, sleep duration, sleep mood and drowsiness during activities. This happens because of the habit of using electronic devices that shine brightly and highlight the eyes, this light can trigger or stimulate the brain to wake up and delay the desire to sleepInsomnia is part of the primary sleep disorder group, dyssomnia. Insomnia is the inability to meet the need for sleep both in quality and quantity due to difficulties in initiating and maintaining sleep. About 30% of adults suffer from insomnia, and 10% of adults suffer from severe insomnia. The purpose of this article is to determine the impact of gadget on the incidence of insomnia. The method used is systematic literature review. The result of this literature review is that the use of devices has an impact on the incidence of insomnia. The use of electronics deals with various aspects of sleep such as sleep quality, sleep duration, sleep mood and drowsiness during activities. This happens because of the habit of using electronic devices that shine brightly and highlight the eyes, this light can trigger or stimulate the brain to wake up and delay the desire to sleep